Citrus bergamia essential oil: from basic research to clinical application - Navarra, Michele; Mannucci, Carmen; Delbò, Marisa; Calapai, Gioacchino (Frontiers in Pharmacology, 2015)
Citrus bergamia Risso et Poiteau, also known as “Bergamot”, is a plant belonging to the Rutaceae family, defined as a hybrid of bitter orange and lemon. It is an endemic plant of the Calabria region (Italy). Bergamot fruit is primarily used for the extraction of its essential oil (bergamot essential oil: BEO), employed in perfume, cosmetics, food and confections. The aim of this review was to collect recent data from the literature on Citrus bergamia essential oil and, through a critical analysis, focus on safety and the beneficial effects on human health. Clinical studies on the therapeutic applications of BEO exclusively focus on the field of aromatherapy, suggesting that its use can be useful for reducing anxiety and stress.